Civilizational dimensions of the fatwa of competent jihad A reading of the book “Glimpses of the Modern History of Iraq” by Dr. Ali Al-Wardi - Azarshab, Muhammad (Journal of Kufa Studies Center, 2023)
Civilized reading of history There is no doubt that reading history has to do with the reader's gaze, and the incidents of Islamic history can be read with a positive luminous outlook and can also be read with a dark negative outlook. Revolutions in the Islamic world, from the revolution of Hussein bin Ali (pbuh) to the contemporary revolutions in the Islamic world, have been read in two ways, and so is the case with the popular movement and uprising. A positive and luminous reading is one that stands at the ability of religion to explode energies and push the nation towards demanding its pride and dignity. It focuses on the ability of religion to dissolve national, sectarian and regional barriers, and to unite hearts, ideas and steps in social mobility. It shows the ability of a faithful religious leadership to break the chains of intimidation, terror and falsification. It illustrates the ability of religion to build as well as its ability to destroy. It highlights the role of the religious authority in warning against falling into the pitfalls of deviation, falling into sedition and in the traps of the enemies of Islam. It also demonstrates its role in defending the political, economic and cultural interests of Muslim peoples. While the negative reading otherwise focuses on discord, conflict, narrow self-interest, and attitudes that it describes as wrong and backward in socio-religious mobility. We have seen these two types of reading in the positions of the religious authority in our days, and therefore examples also from the fatwas of jihad al-Kafa'i in the modern era, some of which we stop at based on what he mentioned from the documents of Dr. Ali Al-Wardi in his book "Social Glimpses of the Modern History of Iraq", and our comment on them based on a positive civilized view.